3D culturing as a promising strategy to enhance the angiogenic potential of adipose stem cell-derived secretome: insights into the role of miR-145-5p/ANGPT2 axis - G. Gerini; E. Mari; P. Pontecorvi; S. Camero; E. Romano; D. Ranieri; F. Megiorni; P. Fioramonti; A. Angeloni; C. Marchese; S. Ceccarelli (Stem Cell Research & Therapy)
Abstract Background Adipose-derived mesenchymal stem cells (ASCs) represent a valid therapeutic option for clinical application in several diseases, mostly due to the paracrine activity of their secretome, exerting pro-angiogenic, antinflammatory and immunosuppressive effects. Recently, 3D culturing models has been shown to significantly influence the intrinsic characteristics of these cells, their gene expression and the secretome’s composition, thus affecting ASC paracrine effects and clinical potential. This study aims to investigate the feasibility of exploiting 3D culturing as a tool to improve ASC secretome therapeutic efficacy. Methods ASCs were cultured in monolayers via conventional two-dimensional (2D) methods or induced to form 3D spheroids by seeding them on 96-well ultra-low attachment (ULA) plates. The phenotypical characterization of 3D-ASCs was performed through immunofluorescence analyses. The composition and angiogenic potential of 3D-ASC-derived secretome was assessed by means of protein array and functional tube formation assay, respectively. We analyzed the expression profile of 92 angiogenesis-related genes in 2D versus 3D cultures through a qRT-PCR array, and GO term enrichment analysis followed by network analysis was applied to identify the top hub genes. The expression of specific angiomiRs in 3D-ASCs and their secretome was assessed by qRT-PCR. The role of miR-145-5p was investigated through transfection with specific mimics/anti-miR. Results 3D-ASCs showed increased stemness, cell–cell and cell-ECM interactions with respect to 2D-cultured cells. 3D culturing increased the secretion of cytokines involved in the promotion of angiogenesis, resulting in improved angiogenic effects on HUVEC cells. Mechanistically, qRT-PCR array data indicated downregulation of angiopoietin-2 (ANGPT2) as a key factor in the 3D-ASC-secretome-induced angiogenesis. In addition, ANGPT2 was recognized as a predicted target of miR-145-5p, one of the angiomiRs found upregulated in 3D-ASCs. Depletion of miR-145-5p significantly altered ASC secretome angiogenic potential and ANGPT2 expression on HUVEC cells. Conclusions All these findings corroborate our hypothesis that 3D culturing is able to positively modulate ASC gene expression and secretome composition in terms of pro-angiogenic potential. Indeed, our study contributes to shed light on the role of the miR-145-5p/ANGPT2 axis in this process, opening the way to innovative potentiation strategies to implement secretome-based therapies, with broad clinical applications.